Optimal resection rate for lung cancer in the UK: how high should we go? - Najib Rahman; Elizabeth Belcher; Dionisios Stavroulias; Jenny Mitchell; Francesco Di Chiara (BMJ Open Respiratory Research)
Background The optimal resection rate for institutions managing early-stage primary lung cancer is not known. Whether the prognosis of patients who do not proceed to operation is determined by their comorbidities for which they were deemed at prohibitively high-operative risk, or disease progression, is uncertain. We investigated the outcomes of patients with early-stage lung cancer who were considered for surgical management.Methods We reviewed the outcomes of consecutive patients who were considered for resection of early-stage primary lung cancer at Oxford University Hospitals National Health Service Foundation Trust between 2012 and 2017.Results Between 29 November 2012 and 31 March 2017, 467 consecutive patients underwent resection with curative intent for primary lung cancer (operative group), while 81 patients were deemed resectable but either inoperable or did not wish to proceed to operation (non-operative group). Reason for not proceeding to resection was cardiovascular in 16 patients (19.8%), respiratory in 21 (25.9%), cardiorespiratory in 11 (13.6%), performance status in 8 (9.9%) and patient choice in 25 (30.9%) patients. Sixty-six patients (81.5%) received an alternative radical treatment. Median follow-up was 169 weeks (IQR 119–246 weeks) in the operative group and 118 weeks (IQR 74–167 weeks) in the non-operative group. Median survival of patients with early-stage lung cancer who did not proceed to operation was 2.5 years; median survival of patients undergoing lung cancer resection was undefined (p<0.0001). Lung cancer was documented as directly or indirectly leading to or contributing to death in 40 patients (76.9%). In 11 patients, the cause of death was due to comorbidities (21.2%).Conclusions Patients turned down for operation in a high-resection rate UK unit have limited survival due to lung cancer progression. We conclude that ‘optimal’ resection rates may not have been reached in the UK even in high-resection rate centres.